2021
DOI: 10.1016/j.ijme.2019.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurship education, curriculum and lecturer-competency as antecedents of student entrepreneurial intention

Abstract: The high unemployment rate that has become characteristic of the South African economy has generated some spinoffs that bode undesirable consequences, not only for economic development but also for sane social-cultural coexistence of the people. Recourse to entrepreneurship rather than clinging on to an endless hope for formal employment has been touted as a possible antidote for confronting the situation. However, a prerequisite to self-employment is entrepreneurial intention. This study therefore explores fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
168
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 163 publications
(190 citation statements)
references
References 42 publications
15
168
0
7
Order By: Relevance
“…Therefore, in entrepreneurship learning, faculties and universities must provide the best so that students are able to understand entrepreneurship and be able to increase their interest in entrepreneurship. The results of this study are supported by previous research conducted by Iwu et. al.…”
Section: The Effect Of Entrepreneurship Learning On Entrepreneurial Isupporting
confidence: 91%
“…Therefore, in entrepreneurship learning, faculties and universities must provide the best so that students are able to understand entrepreneurship and be able to increase their interest in entrepreneurship. The results of this study are supported by previous research conducted by Iwu et. al.…”
Section: The Effect Of Entrepreneurship Learning On Entrepreneurial Isupporting
confidence: 91%
“… [7] argue that the correlation between perceived university support and entrepreneurial intention is insignificant. Therefore, it has been suggested that this linkage should be further empirically explored [8] . Also, there are limited datasets of primary data which are available to investigate the influence of perceived education supports at universities on attitude towards entrepreneurship, subjective norms, perceived behavioral control, entrepreneurial self-efficacy and entrepreneurial intention among college students.…”
Section: Data Descriptionmentioning
confidence: 99%
“…Furthermore, Manyaka-Boshielo (2019) describes entrepreneurship education as a structured, formal conveyance of entrepreneurial competencies, which, in turn, refers to the concepts, skills and mental awareness used by individuals during the process of starting and developing their growth-orientated business venture. Iwu et al (2019) contend that entrepreneurship education enables the acquisition of entrepreneurial knowledge, skills, attitudes and behaviours. The development of entrepreneurship education is considered a fundamental precondition for augmenting entrepreneurs' innovation skills in a rapidly changing environment (Ndou, Mele & Del-Vecchio 2018).…”
Section: Entrepreneurship Educationmentioning
confidence: 99%